Administracja publiczna jako wyznacznik sprawy z zakresu administracji publicznej - Wilczyńska, Agnieszka (Acta Universitatis Lodziensis. Folia Iuridica, 2009)
In efforts to establish the criteria for identifying a case as that pertaining to public administration (a key issue for delineating the scope of cognition of administrative courts), apart from the analysis of legal relation upon which the case is based, or criteria of the court assigned for a given cognition, it appears necessary to relate to the phenomenon of public administration. Adopting the assumption that one of the features of the term: “public administration case” (not only in semantic approach) is the phenomenon concerned with public administration itself, necessitates rather unambiguous understanding of such administration. To this end, it appears necessary to analyse both the meaning and the scope of the term: “public administration”. The ambiguity of this term within normative, judicatural and doctrinal realms would prevent public administration from being a priori a definitive criterion for identifying a case as that belonging to public administration domain. This paper includes the analysis of an objective and subjective approach to public administration. Within the context of discovering one of the determinants for a public administration case, these dissertations also tackle the issues concerning the criteria and the scope of public administration.